Pengaruh Media Pembelajaran Interaktif Berbasis Adobe Flash Terhadap Minat Belajar IPAS Siswa Kelas IV Sekolah Dasar - Rustan, Nurul Azmy; Susianti; Ramadani, Nurvidyah Zul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the fact that students have low interest and understanding of IPAS (Natural and Social Science) material, caused by uninteresting teaching methods and limited interactive learning media used by teachers. This study aims to determine the application of Adobe Flash-based interactive media in improving the effectiveness of teaching Natural and Social Science (IPAS) at SD 178 Tanalle, Marioriwawo District. This research is classified as experimental research with a quantitative approach. The design used in this study is a quasi-experimental design with the type of nonequivalent control group design. The population in this study is 42 people. The sample consists of 21 students who were selected using purposive sampling technique. Data collection was conducted through questionnaires. The data analysis of this study used an independent sample t-test. The results of the study indicate that the application of interactive media based on Adobe Flash can increase students' interest in learning and understanding of concepts in IPAS learning. This is shown by an increase in the average scores of students' learning interest in each cycle as well as an increase in students' activity and participation during the learning process. The conclusion of this study is that interactive media based on Adobe Flash is effective to be used as a learning aid for IPAS to improve the quality of the learning process and students' interest in learning.